Interactive Learning Media Using Google Sites to Enhance Students’ Understanding of Ratio Concepts in Grade VII - Gina Putri Aulia; Surya Amami Pramuditya (Ar-Riyadhiyyat: Journal of Mathematics Education, 2025)
This study aims to analyze the effectiveness of Google Sites as an interactive learning medium for teaching ratio concepts to Grade VII students. Despite increasing access to digital tools in education, the adoption of web-based platforms like Google Sites remains limited due to technical constraints and a lack of training among teachers. To address this, a learning website was developed using the ADDIE instructional design model (Analysis, Design, Development, Implementation, Evaluation) and implemented through a Research and Development (R&D) methodology. The platform included structured explanations, interactive exercises, videos, and quizzes aligned with the curriculum. A total of 45 students participated in the implementation phase, and their responses were evaluated using a student questionnaire. The results showed that 84.8% of students found the material presented on the Google Site to be clear and easy to understand, and 83.2% reported that it helped them grasp ratio concepts more effectively. The platform was also rated positively for design and navigation (80.8%). However, student motivation for independent learning was relatively lower at 73.8%, indicating the need for further development of interactive and engaging features. These findings suggest that Google Sites is effective in supporting conceptual understanding in mathematics, and its integration with blended learning and gamification strategies is recommended to enhance student motivation and engagement in digital learning environments.